The complete mitochondrial genome of Soriculus nigrescens (Soricomorpha: Soricinae). Issue 2 (3rd July 2019) - Jiang, Haijun; Deng, Wanlu; Wei, Haixue; Wang, Qiong; Chen, Shunde
Abstract: The Himalayan Shrew ( Soriculus nigrescens ) Gray, 1842 belongs to the subfamily Soricinae, which is distributed in southwest China, Nepal, India, and Bhutan. This species is classified as Least Concern on The IUCN Red List. In this study, we sequenced the complete mitochondrial genome of S. nigrescens . This mitogenome is 17, 284 bp in length and contains a set of 13 protein-coding genes (PCGs), two ribosomal RNA genes (rRNA), 22 transfer RNA genes (tRNA), one origin of L strand replication, and one control region. In order to explore the molecular phylogenetics evolution of Soricinae, the nucleotide sequence data of 13 PCGs of S. nigrescens and other 17 Insectivores were used for the phylogenetic analysis.